Religion, religiosity, and communalism - Bidwai,Praful (Editor) Harbans Mukhia (Editor) Achin Vanaik (Editor) (Manohar Publishers & Distributors, 1996)
Contributed papers on the communal problem in India, chiefly with reference to Hindu and Muslim.